Plasma renin concentration represents an independent risk factor for mortality and is associated with liver dysfunction in patients with cirrhosis. Issue 1 (January 2017) - Paternostro, Rafael; Reiberger, Thomas; Mandorfer, Mattias; Schwarzer, Remy; Schwabl, Philipp; Bota, Simona; Ferlitsch, Monika; Trauner, Michael; Peck‐Radosavljevic, Markus; Ferlitsch, Arnulf
Abstract: Background and Aim: Plasma renin concentration (PRC) is increased in patients with cirrhosis. The aims of this study were to evaluate the relation of PRC to (i) portal hypertension, (ii) degree of liver dysfunction, and (iii) survival. Methods: Plasma renin concentration (range 2.8–39.9 μU/mL) was measured after 30 min in supine position. Also, hepatic venous pressure gradient (HVPG), Child–Pugh (CPS), model for end‐stage liver disease scores and transient elastography values (TE, Fibroscan) were evaluated at this time. Mortality was recorded during follow‐up. Results: One hundred fifty cirrhotic patients (age 55 ± 11 years; 73% male; CPS A 41.3%/B 41.3%/C 17.3%) were included. Mean HVPG was 16.6 ± 6.5 mmHg. Median PRC according to CPS was A 15.45 μU/mL (95%CI 1.56–261.5), B 37.3 μU/mL (95%CI 4.29–1317.65), and C 175.3 μU/mL (95%CI 5.3–5684; P < 0.001). In patients with clinical significant portal hypertension (HVPG ≥ 10 mmHg, n = 123) median PRC was 31.2 μU/mL (95%CI 2.76–1345.4), in those without was 13.7 μU/mL (95%CI 2.7–428.2; P = 0.009). Significantly higher TE values (33.2 [13–75] vs 59.65 kPa [14.5–75]; P = 0.014) were found in patients with elevated PRC. Median follow up was 711 days (95%CI 24–1152). Twenty‐two (36.1%) of the 61 patients with elevated PRC and 11 of the 89 (12.4%) with normal PRC died ( P = 0.001). Median PRC was significantly higher in patients that died (83.6 μU/mL [3.39–4451.9] vs 21.5 μU/mL [2.6–1197.9]; P = 0.001). Elevated PRC ( P = 0.005; HR 3.36; 95%CI 1.46–7.85), hepatocellular carcinoma ( P < 0.001; HR 10.68; 95%CI 3.64–31.3), CPS B ( P = 0.013; HR 3.69; 95%CI 1.31–10.4) and CPS C ( P = 0.008; HR 5.36; 95%CI 1.54–18.62) emerged as independent risk factors for mortality. Conclusions: In cirrhotic patients PRC correlates with the severity of portal hypertension and liver dysfunction. Moreover, elevated PRC represents an independent risk factor for mortality.